PENGEMBANGAN SOAL MATEMATIKA TIPE PISA MENGGUNAKAN KONTEKS PURI TRI AGUNG - M. Noviarsyah Dasaprawira; Riski Aspriyani (Prodi Pendidikan Matematika, STKIP PGRI Bandar Lampung, 2020)
This study aims to develop a math problem type PISA to familiarize students using problems with PISA standard and produces a valid, practical, PISA context of Puri Tri Agung type and see the basic math skills (KDM) seen from the context of Puri Tri Agung. The research method used is design research with the type of research development. The result of the research is a valid PISA math problem at the expert review stage and one to one, while the practicality is done by small group stages. Ability that is found in the form of communication, representation, mathematical, reasoning and argument, and formulate strategy to solve the problem.